Toronto Workers' History Project: The Story Continues (2017)
Mission statement: The Toronto Workers History Project (TWHP) is a large group of workers, unionists, professors, students, artists, teachers, librarians, educators, researchers, community activists, and retirees dedicated to the preservation and promotion of the history of working people in Toronto. We are committed to bringing to light the experiences of working people and their contributions as individuals and collectively to the building of this city, in the home, in the paid workplace, and in the community. We want to highlight the vitality and creativity of working-class cultures in the history of Toronto. We are determined to include the full diversity of working-class experience, including women, indigenous people, racialized people, people with disabilities, and gays, lesbians, and trans people. We embrace the histories of people from all parts of the world. We aim to make these stories available through a variety of media for audiences of all ages and backgrounds. We want to educate the people of Toronto and beyond, but also to inspire activists in social-justice and labour movements with the lessons from the past for the struggles to change the world today.

Chinese Legacy BC - Province of British Columbia - Ministry of International Trade (2017)
On May 15, 2014, the Government of British Columbia apologized to its Chinese Canadian community for historical wrongs. It also committed to provide a legacy for all British Columbians so that we can learn more about a time we cannot and should not forget. This website is a part of that legacy. It offers resources that document the history of the discrimination, chronicle the consultation process and formal Apology in the Legislature, and provide updates on the many legacy projects that highlight the substantial contributions Chinese Canadians have made to the culture, history and economic prosperity of our province. --Website description